Checklist of earthworms (Oligochaeta: Lumbricidae) from Germany - Lehmitz, Ricarda; Römbke, Jörg; Jänsch, Stephan; Krück, Stefanie; Beylich, Anneke; Graefe, Ulfert (Zootaxa, 2014)
A checklist of the German earthworm fauna (Oligochaeta: Lumbricidae) is presented, including published data, data from reports, diploma- and PhD- theses as well as unpublished data from museum collections, research institutions and private persons. Overall, 16,000 datasets were analyzed to produce the first German checklist of Lumbricidae. The checklist comprises 46 earthworm species from 15 genera and provides ecological information, zoogeographical distribution type and information on the species distribution in Germany. Only one species, Lumbricus badensis Michaelsen, 1907, is endemic to Germany, whereas 41% are peregrine. As there are 14 species occurring exclusively in the southern or eastern part of Germany, the species numbers in German regions increase from north to south.